Validity of the VmaxST portable metabolic measurement system - Laurent, C. M.; Meyers, M. C.; Robinson, C. A.; Strong, L. R.; Chase, C.; Goodwin, B. (Journal of Sports Sciences, 2008)
The aim of this study was to assess and compare the validity of the portable VmaxST telemetry metabolic measurement device with that of a standard measurement system (Vmax29). Thirty asymptomatic, moderately active males provided written, informed consent and completed two maximal graded treadmill exercise tests (Bruce) using the VmaxST and the Vmax29 metabolic measurement systems. Tests were performed in random order on separate days to obtain peak values for time to exhaustion, heart rate, systolic and diastolic blood pressure, oxygen consumption (VO2); carbon dioxide production (VCO2), ventilation (VE), and respiratory exchange ratio (RER). Multivariate analysis of variance revealed no significant main effect (P = 0.88) between the two systems across any variable, suggesting similar measurement capabilities between the two systems. Linear regression analyses revealed moderate to high coefficients of determination for VO2 (r2 = 0.99), VCO2 (r2 = 0.99), VE (r2 = 0.99), and RER (r2 = 0.89). Furthermore, Bland-Altman analyses demonstrated that the VmaxST yielded similar values to the Vmax29, suggesting good agreement between the two systems. Agreement was confirmed when the differences between the methods resulted in a small range as identified by the 95% limits of agreement. Findings from the current study confirm that the VmaxST is a valid device for measuring metabolic and physiological variables during exercise within a controlled laboratory setting.